Is there a bubble in the Chinese housing market? - Christian Dreger; Yanqun Zhang (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
For many analysts, the Chinese economy is spurred by a bubble in the housing market, probably driven by the fiscal stimulus package and massive credit expansion, with pos-sible adverse effects to the real economy. To get insights into the size of the bubble, the house price evolution is investigated by panel cointegration techniques. Evidence is based on a dataset for 35 major cities. Cointegration is detected between real house prices and a set of macroeconomic determinants, implying that a bubble exhibits mean-reverting behaviour. The results indicate that the bubble is about 25 percent of the equi-librium value implied by the fundamentals at the end of 2009. The bubble is particularly huge in the cities in the southeast coastal areas and special economic zones. While the impact of real house prices on CPI inflation appears to be rather strong, GDP growth may not be heavily affected. Thus, a decline of the bubble will likely have only modest effects on the real economy.
Keywords: G12; R21; C33; 330; Chinese economy; panel cointegration; house price bubbles